Ada Apa dengan Tax Avoidance di Indonesia? - Rahayu; Nur Wulandari; Ghaliah Jalwaa Insyirah Zainal (Journal of Economic Education and Entrepreneurship Studies, 2023)
The purpose of this study is to identify, assess and provide interpretation of the results of the condition of tax avoidance in Indonesia and the potential - the potential behind the occurrence of tax avoidance or tax avoidance in Indonesia. The method used in this research is a qualitative meta-analysis method of several findings related to tax avoidance. The process of analysis with meta-analysis is carried out with the stages of formulating research problems, exploration, data search, determining appropriate data, and controlling quality. The results showed that the potential managerial and operational conditions of the company, the characteristics of the company and the inequality of the system and performance and Indonesian tax law are potentials that can make the continuation of the phenomenon of tax avoidance in Indonesia. The synergy of managerial improvement by the company, supervision of company characteristics, improvement of systems, laws and performance, by the government and equality of views between taxpayer actors and the government are things that must be done to suppress the phenomenon of tax avoidance in Indonesia.